Volatile Components of the Essential Oil ofPrangos asperulafrom West of Iran - HADAVAND MIRZAEI, HOSSEIN; RAMEZANI, ZIBA (Asian Journal of Chemistry, 2010)
The essential oil of the Prangos asperula was collected in Lorestan province west of Iran and was extracted by hydrodistillation method from aerial part and identified using GC/MS as the method of analysis. 42 Components were characterized for the Prangos asperula oil. The major components of the oil were α-pinene (13.6 %), limonene (12.94 %), myrcene (8.1 %), β-pinene (5.4 %), δ-3-carene (25.54 %), α-terpinolene (14.76 %), caryophylene (2.98 %) and γ-curcumene (2.65 %).